Pyrolysis of oil-plant wastes in a TGA and a fixed-bed reactor: Thermochemical behaviors, kinetics, and products characterization. (September 2015) - Chen, Jianbiao; Fan, Xiaotian; Jiang, Bo; Mu, Lin; Yao, Pikai; Yin, Hongchao; Song, Xigeng
Graphical abstract: Highlights: Pyrolysis of four distinct oil-plant wastes was studied by TGA and fixed-bed reactor. Effects of biomass species and heating rates on pyrolysis behaviors were evaluated. Products distribution, gas compositions, and chars surface chemistry were analyzed. Kinetics was analyzed by CR method, and the kinetic compensation effect was evident. Abstract: Pyrolysis characteristics of four distinct oil-plant wastes were investigated using TGA and fixed-bed reactor coupled with GC. TGA experiments showed that the pyrolysis behaviors were related to biomass species and heating rates. As the heating rate increased, TG and DTG curves shifted to the higher temperatures, and the comprehensive devolatilization index obviously increased. The remaining chars from TGA experiments were higher than those obtained from the fixed-bed experiments. The crack of tars at high temperatures enhanced the formation of non-condensable gases. During the pyrolysis, CO and CO2 were the major gases. Chars FTIR showed that the functional groups of OH, CH n, CO, CO, and CC gradually disappeared from 400 °C on. The kinetic parameters were calculated by Coats–Redfern approach. The results manifested that the most appropriate pyrolysis mechanisms were the order reaction models. The existence of kinetic compensation effect was evident.